Von Willebrand Disease in Colostomy Stoma Closure – A Case Report of Perianaesthetic Management (Journal of the Bangladesh Society of Anaesthesiologists, 2019)
Von Willebrand disease (VWD) is the most common inherited bleeding disorder that is caused by deficiencyor dysfunction of von Willebrand factor (VWF), a plasma protein that mediates the initial adhesion ofplatelets at sites of vascular injury and also binds and stabilizes blood clotting factor VIII (FVIII) in thecirculation.1 The prevalence of VWD is about 1% of the population & approximately twice in female thenman because of their unique potential of menorrhagia.2 We are reporting a successful perioperativeanaesthetic management of 33year female, a known case of Von Willebrand disease (VWD) who underwentroutine colostomy closure.JBSA 2019; 32(2): 50-53